Diversity of Plant Growth Promoters (PGP) Isolated from Agricultural Fields of Bangladesh - Habib, Halima; Trishna, Shammi Akhter; Begum, Anowara; Akhter, Humaira (Bangladesh Journal of Microbiology, 2024)
With an emphasis on leguminous plants like Glycine max (soybean), Clitoria ternatea, and non-leguminous plants like Phaseolus lunatus, this study investigates the diversity of Plant Growth-Promoting Rhizobacteria (PGPR) isolated from the root nodules and rhizospheres of agricultural soil. Seventeen of the 42 isolates were chosen for further analysis. Isolates were screened through phenotypic characterization, presumptive identification, and evaluation of their plant growth-promoting (PGP) qualities. Amplification of the nitrogen[1]fixing nifH gene, the nodulation-inducing nodC gene, and the 16S rRNA were among the molecular investigations carried out. Three examined PGP features were present in 35% of the isolates, according to the results. From pH levels of 4.5 to 9, temperatures of 37oC to 40oC and salt concentrations of 1% or less, the isolates showed versatility in a variety of environmental circumstances. Resistant to high temperatures (40°C), slow-growing rhizobia (22%) were shown to be sensitive to high pH (9). Tilt and Tafgor pesticides had a more severe influence on PGP traits and development than Shadhin G and Semcup. The design and efficacy of biofertilizers, agro-economic progress, and sustainable agriculture are among the topics on which this qualitative study sheds important light. Bangladesh J Microbiol, Volume 40, Number 2, December 2023, pp 66-74